Writing Error Analysis in Exposition Text of the EFL Junior High School Students - Fauzan, Umar; Aulya, Sapna Farah; Noor, Widya Noviana (Indonesian Journal of EFL and Linguistics, 2020)
The objective of this research was to understand the writing error of eleventh-grade students of SMA Negeri 4 Samarinda. The descriptive qualitative method was used to examine the written exposition text made by 15 students. The data was collected from the participants’ writing on exposition text and analyzed based on the errors’ categorization. The result showed that there are 16 categories of errors found in the data. They were punctuation, missing word, capitalization, subject-verb agreement, pronoun agreement, spelling, singular or plural, unnecessary word, wrong word form, wrong word, wrong order, fragment, preposition, conjunction, article, and need-further support error. The error factors were intralingua transfer, interlingua transfer, and students’ lack of knowledge about writing.